2019
DOI: 10.4236/ojpchem.2019.94008
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Modification of Nanocellulose in Wood Adhesive: Review

Abstract: Bio-based nanomaterial is more attractive, due to its abundance, eco-friendliness and sustainability, when compared to the non-renewable toxic petrochemicals used in the wood adhesive sector. Recent studies on the formaldehyde emission by petrochemical binders in wood adhesives have attracted scientists for the research in biomaterial-based binders. In this aspect nanocellulose (NC) is one such material which has reinforcing ability and has natural binding properties. Conventional wood adhesive uses petrochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 68 publications
2
25
0
Order By: Relevance
“…There are few reports which studied on the application of nanocellulose in wood adhesives (Lengowski et al, 2019;Vineeth et al, 2019). Commonly, wood adhesives can be classified into two big groups, which are soft and brittle adhesive.…”
Section: Nanocellulose In Wood Adhesivesmentioning
confidence: 99%
See 2 more Smart Citations
“…There are few reports which studied on the application of nanocellulose in wood adhesives (Lengowski et al, 2019;Vineeth et al, 2019). Commonly, wood adhesives can be classified into two big groups, which are soft and brittle adhesive.…”
Section: Nanocellulose In Wood Adhesivesmentioning
confidence: 99%
“…Kwon et al, 2015 MFC Up to 5 UF The addition of MFC indicated lower thermal stability at different F/U mol ratio except the enhancement of thermal stability at low F/U mol ratio which is 0.9 (E0). Nuryawan et al, 2017 (vinyl alcohol) may increase the performance and mechanical features, opening new possibilities for eco-friendly and bio-based wood adhesives (Vineeth et al, 2019). These achievements can reduce the dependency of petrochemicals in wood adhesives field in the near future.…”
Section: Nanocellulose In Wood Adhesivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Conceptually, NC can be produced by a top-down hydrolysis methodology through different steps, that is, (i) pretreatment processes of lignocellulosic biomass employing physical approaches concerning crushing, screening, washing and cooking to eliminate coarse particles, oily content and dust from the material surface, (ii) removing extractive/hemicellulose/lignin via chemical, physical, physicochemical, biological or the combination of two or more treatments, (iii) fragmentation and cleavage of cellulosic elementary fibrils or micro-fibrils to generate nanofibers through various approaches and (iv) post-treatments such as solvent removing, dialysis, sonication, centrifugation, surface modification, stabilization and drying. The three latter steps have received great interest from the scientific community for designing products with desired features [ 12 , 13 , 23 , 27 , 38 , 67 , 68 , 69 , 70 , 71 , 72 , 73 ]. NC possesses excellent useful properties such as renewability, eco-friendliness, biocompatibility, non-toxicity, hydrogen-bonding capacity, tunable crystallinity, high chemical resistance, tailored aspect ratios (100–150), low thermal expansion coefficient, reactive surface, low density (1.6 g/cm 3 ), high specific surface area (100–200 of m 2 /g), high tensile strength (7.5–7.7 GPa) and elastic modulus (130–150 GPa) [ 10 , 30 ].…”
Section: Cellulose Nanocrystals (Cnc)mentioning
confidence: 99%
“…This could be attributed to the cross-linking reaction between CNC and GA via hydrogen bonding. [25][26][27] Besides, the crosslinking reaction between chitosan and glutaraldehyde could increase the activation energy due to the reduced chain mobility of cross-linked network and hence, higher amount of energy was required for cross-linking of the reactants. [28] Similar finding was reported by Correia et al [29] in which the activation energy was increased for cross-linked samples.…”
Section: Degree Of Cross-linkingmentioning
confidence: 99%